Follicle development and selection: past, present and future - Webb, R.; Buratini, J. [UNESP]; Hernandez-Medrano, J. H.; Gutierrez, C. G.; Campbell, B. K. (Brazilian Coll Animal Reproduction, 2016)
This paper reviews progress that has been made over the last 50 years and discusses how the development and application of new technologies have been utilized to increase our understanding of the development and selection of the dominant follicle. Our increased knowledge from research carried out worldwide, has demonstrated that the development of the dominant follicle, and importantly the production of a good quality oocyte, are controlled by a set of complex and interactive extra-and intra-ovarian control systems, impacted by underlying genetic and external environmental factors, such as nutrition. In totality this has resulted in improvements in fertility, as demonstrated by the impact of diet on oocyte quality and increased pregnancy rates. However, given the increasing global challenges of food security, coupled with climate change, more in-depth understanding of these complex multifactorial control systems will have even greater significance in overcoming today's livestock production challenges, including some that were present over 50 years ago. In conclusion, the continuing development of new technologies, coupled with new knowledge and understanding of these complex control systems, should ensure that ruminant fertility is maximized, while ensuring good animal welfare within sustainable production systems.
Keywords: cattle; follicle; ovary; reproduction